Immunologic deviations in recurrent spontaneous abortion mouse model. (19th October 2022) - Ansariniya, Hossein; Zare, Fateme; Mosaffa, Nariman; Idali, Farah; Shabani, Mahdi; Hadinedoushan, Hossein
Abstract: Background: Recurrent spontaneous abortion (RSA) or recurrent pregnancy loss (RPL) is an abnormality that has a great impact on women's quality of life. RSA is defined as at least three unexplained abortions (without prior live birth) occurring before the 20th week of pregnancy. Aim: The present review attempts to discuss immunologic deviations in mouse models of RSA. Content: The mating of DBA/2J males with CBA/J female mice has provided specialists with a homologous model of RSA. Much of the research using the CBA/J × DBA/2J mouse model has shown immune system alteration results in rejection. The link between RSA and the immune system suggests new approaches to prevent RSA from an immunological perspective. Rejection in this model is linked with the changed immune system during pregnancy, including change in Th1/Th2 ratio and defects in T and NK cells function, and so forth. Implications: The use of animal models prone to RSA can help a lot to solve the remained mysteries. This study reviews the existing knowledge of immune system roles in the RSA mouse models.